Capsule endoscopy and deep enteroscopy - Gerson, Lauren B. (Endoscopy, 2013)
Abbreviations: CO2, carbon dioxide; DBE, double-balloon enteroscopy; MGCE, magnetic-guided capsule endoscopy; PC, patency capsule; PEG, polyethylene glycol; SBE, single-balloon enteroscopy; VCE, video capsule endoscopy